Competencies and Service Quality of a Private Non-Sectarian University In Cebu City, Philippines - Marlon Rael Astillero; Tri Febrianti Valentina; Nico Irawan (Universitas Muhammadiyah Sidoarjo, 2020)
This study was to determine the competencies and service quality of government employees teaching part-time at the university. The study collected data on the assessment of the teachers about skills and students regarding the service quality of their teachers in a private non-sectarian university in Cebu City, Philippines. The part-time teachers in the university have extremely high competencies in methodology, motivation, material utilization, instructional process, teaching evaluation, and interaction process. As these college teachers gain experience both in school as teachers and as government employees, they are also enriching their ability and commitment to teaching and for the goal of quality education. The quality of their services is learned through their readings research and self-learning activities as part of their continuing education. The level of competencies among the part-time teachers in the university is not significantly associated with their service quality delivery.